EVALUATION OF BUSINESS FEASIBILITY AND IMPACT OF LOCAL INNOVATION ON IMPROVING COFFEE QUALITY IN GARUT REGENCY PRODUCTION CENTER - Suryana, Dadan; Tridakusumah, Ahmad Choibar; Charina, Anne (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
This study aims to analyse the financial feasibility of the ground coffee production business undertaken by coffee farmers and processors by applying local innovations at the cultivation, post-harvest handling, and coffee processing stages in the coffee production centre of Garut Regency. This study used a quantitative approach to provide a comprehensive understanding of the feasibility of the ground coffee business with local innovations applied by coffee farmers and processors in Garut Regency. Local innovations in coffee production include pruning techniques, grafting, solar dryer dome technology for herbal coffee making, the use of local roasting machines, and the utilization of coffee waste into value-added products such as ceramics, organic fertilizer, and dodol. Quantitative analysis of coffee processing business feasibility based on NPV value of Rp 38,394,163, Gross B/C 1.08, Net B/C 1.25, IRR 17.73 percent, payback period 7.7. These results showed that the business carried out by ground coffee processors in the production centre area is feasible. These results of the sensitivity analysis show that an increase in the price of coffee fruit raw materials at a limit of 16.67 percent and a decrease in ground coffee production at a limit of 11.37percent still produces a positive value and the business is still feasible. These results of the switching value analysis explain that the tolerance limit for the increase in the price of coffee fruit raw materials can be tolerated if the rise is no more than 26.66 percent and the decrease in ground coffee production does not exceed 7.023percent if it exceeds within 1 year then the business is not feasible.